the TEACHER COGNITION AND CURRICULUM CHANGE: HOW NON-NATIVE ENGLISH TEACHERS PERCEIVE DEEP LEARNING IMPLEMENTATION IN EFL CLASSROOMS - Adib Hassan Abdillah; Ateng Kurnia; Mohammad Soni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia's shift from the 2013 Curriculum to the Merdeka Curriculum has repositioned deep learning, anchored on mindful, meaningful, and joyful learning, as the pedagogical core of classroom practice, including English as a Foreign Language (EFL) instruction. Because most Indonesian English teachers are non-native English teachers (NNETs) serving as both language models and curriculum agents, their cognition, the beliefs and knowledge shaping instructional decisions (Borg, 2003), plays a decisive role in translating policy into classroom enactment. This study investigated how junior high school NNETs perceive and enact deep learning integration under the Merdeka Curriculum. A qualitative case study was employed with two NNETs teaching Grade VIII and Grade IX English at a public junior high school in West Java, purposively selected. Data were collected through semi-structured interviews, classroom observation, and document analysis, then analyzed using Miles, Huberman, and Saldana's interactive model and interpreted through Borg's framework. Findings show both teachers conceptualize deep learning through the mindful-meaningful-joyful triad and align lesson planning with the Capaian Pembelajaran-Alur Tujuan Pembelajaran (CP-ATP) framework through collaborative teacher communities. Observation corroborated their reported facilitative, student-centered practices, including contextual prompting, collaborative and game-based tasks, error tolerance, and appreciation-first feedback. However, both reported persistent self-doubt about their English proficiency, heavier workload from differentiated instruction, and students' affective barriers as major constraints, mitigated through continuous professional development. The study concludes that NNET cognition, shaped by training, professional community, and lived experience as English learners, bridges the gap between curriculum policy and classroom enactment, though sustained institutional support remains essential.